Transcriptomic analysis of aggressive meningiomas identifies PTTG1 and LEPR as prognostic biomarkers independent of WHO grade - Schmidt, Melissa; Mock, Andreas; Jungk, Christine; Sahm, Felix; Ull, Anna Theresa; Warta, Rolf; Lamszus, Katrin; Gousias, Konstantinos; Ketter, Ralf; Rösch, Saskia; Rapp, Carmen; Schefzyk, Sebastian; et al. (OncoTarget, 2016)
https://doi.org/10.18632/oncotarget.7396 Melissa Schmidt, Andreas Mock, Christine Jungk, Felix Sahm, Anna Theresa Ull, Rolf Warta, Katrin Lamszus, Konstantinos Gousias, Ralf Ketter, Saskia Roesch,...